Numerical Modeling of Water and Gas Transport in Compacted GMZ Bentonite under Constant Volume Condition - Jiang-Feng Liu; Xu-Lou Cao; Hong-Yang Ni; Kai Zhang; Zhi-Xiao Ma; Li-Ke Ma; Hai Pu (Geofluids)
During deep geological disposal of high-level and long-lived radioactive waste, underground water erosion into buffer materials, such as bentonite, and gas production around the canister are unavoidable. Therefore, understanding water and gas migration into buffer materials is important when it comes to determining the sealing ability of engineered barriers in deep geological repositories. The main aim of our study is to provide insights into the water/gas transport in a compacted bentonite sample under constant volume conditions. The results of our study indicate that water saturation is obtained after 450 hours, which is similar to experimental results. Gas migration testing shows that the degree of water saturation in the samples is very sensitive to the gas pressure. As soon as 2 MPa or higher gas pressure was applied, the water saturation degree decreased quickly. Laboratory experiments indicate that gas breakthrough occurs at 4 MPa, with water being expelled from the downstream side. This indicates that gas pressure has a significant effect on the sealing ability of Gaomizozi (GMZ) bentonite.